Surveying attitude and use of institutional repositories (IRs) by faculty in agriculture disciplines: a case study (2014)
Over the last few years there has been increase in awareness of the importance of institutional repositories (IRs) in scholarly communication in tertiary institutions. However, low participation of faculty in contributing their intellectual products has been a great concern because it has not allowed institutional repositories to achieve its full potentials. Awareness and attitude among others are factors affecting the use of IR. This paper examines the level of awareness, attitude to use of institutional repositories and challenges faced by faculty in Agriculture disciplines in Federal University of Technology, Akure, (FUTA) Nigeria. Survey method was adopted; data was collected through questionnaire and analyzed using descriptive statistics. The study integrated diffusion of innovation (DOI) and theory of reasoned action (TRA) to understand the awareness and attitude to use of IR. The findings suggest that the level of awareness about IRs by faculty members is increasing; however, there was variation in the level of awareness across agriculture disciplines. In addition, there seems to be general positive attitude to IR, yet there was low submission of scholarly works by faculty. Finally, it was revealed that the use of IR is jointly determined by level of awareness and attitude